Development of Multiple Intelligence-Based Indonesian Learning E-Modules for Grade V Elementary School - Garib Firman Buaga; Supartinah Supartinah (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2025)
Multiple intelligences-based e-modules are digital teaching materials designed to accommodate learners' various learning styles and intelligences to meet diverse learning needs. This module is structured with a more interactive and varied approach to increase learners' involvement in learning. This study aims to develop e-modules based on multiple intelligences in Indonesian language subjects for grade V elementary school and assess the feasibility of the module in supporting the learning process. This study used a research and development method with the ADDIE development model, which consists of the stages of analysis, design, development, implementation, and evaluation. However, this research was carried out up to the validation stage to test the feasibility of the developed product. Validation was conducted through qualitative and quantitative data analysis, involving material experts and media experts as evaluators. The validation results show that the developed e-module has a very high feasibility level, scoring 93% from material experts and 95% from media experts. Based on the research results, it can be concluded that the developed multiple intelligences-based e-module is an alternative teaching material that effectively improves the quality of learning and supports the diversity of students' learning styles. The use of this e-module is expected to facilitate a learning process that is more adaptive, more interactive, and more aligned with the characteristics and needs of elementary school students.